Human Resource Management Practices As Corporate Entrepreneurship Enablers At A Telecommunications Entity In South Africa - Asoba, Samson Nambei; Mefi, Nteboheng Patricia (Journal of Ecohumanism, 2025)
In the context of highly changing business practices, the HRM is also facing turbulence and is having new expectations from its stakeholders. In particular the need for an entrepreneurial outlook of the HRM function is rapidly emerging. The purpose of this study was to explore HRM practices that are enablers of corporate entrepreneurship. The study adopted the philosophy of pragmatism and collected quantitative data. A top ranked organisation in the telecommunications sector was identified for the collection of data. With the assistance of the Managers of the organisations a survey questionnaire was issued to 300 employees of the entity to complete. The questionnaire required respondents to indicate their agreeableness on the adoption or implementation of certain HRM strategic activities in the entity after which Exploratory Factor Analysis was performed to reduce the many practices in to underlying constructs. The study found seven factors as HRM practices for corporate entrepreneurship and these are: (1) autonomy and empowerment, (2) provision of resources, (3) reward structure, (4) training and development programs, (5) continuous learning and adaptation, (6) capability to attract proactive and innovative people and (7) organisational competitive advantage. Organisations are recommended to strengthen their HRM practices for improved corporate entrepreneurship.